A Novel Hempcrete utilizing Calcium Aluminate Cement as a Binder - Nivetha, V.; Muthuraj, M. P. (Engineering, Technology & Applied Science Research, 2025)
Hempcrete is an eco-friendly, carbon-negative building material composed of hemp shives, a binder, and water. While traditionally bound with lime, its mechanical limitations hinder structural applications. This study explores the use of Calcium Aluminate Cement (CAC) as an alternative binder to enhance hempcrete’s mechanical properties. Results indicate that CAC improves early strength, reduces setting time, and enhances compressive, flexural, and elastic properties compared to lime-based hempcrete. Microstructural analysis reveals denser packing and reduced porosity in CAC-based hempcrete, contributing to higher strength. However, CAC increases material costs and affects thermal and acoustic properties due to its density. Despite these challenges, CAC-based hempcrete is promising for applications requiring faster setting, higher strength, and improved durability, though further modifications, such as aggregate additions and compaction, may optimize performance.